The Attitude of Teachers and Parents of Students towards the Implementation of School Management Committee (SMCs) at Elementary Level (International Journal of Theory and Application in Elementary and Secondary School Education, 2019)
The main purposes of the present study were to analyze the attitude of the teachers and parents towards the implementation of School management Committee as elementary level and to examine the significant difference in the attitude of parents (rural and urban) and teachers (male and female). The descriptive survey method was adopted for conducting research, where 20 elementary schools (10 rural and 10 urban) of Sambalpur district, Odisha were taken, from which 160 samples were selected randomly composing both parents and students as a whole. A five-point attitude scale was prepared for collecting relevant data from the sample groups, and the simple percentage technique and ‘t’ test was applied to analyse the obtained data. The findings of the study revealed that Majority of parents and teachers agreed that the formation of the School management Committee at the elementary level is a good step taken by the Government. Both rural and urban parents differed significantly in their attitude towards the implementation of the School Management Committee. In comparison to rural and urban parents, rural parents had a more favourable attitude than urban parents towards SMC. There was no sign of the difference between male and female teachers towards the implementation of the School Management Committee. Both showed an equal favourable attitude.